NMR studies on mechanically oscillating samples under magnetic field gradients - Alves, Felipe Pereira (2023)
Logging While Drilling (LWD) operations take place within highly complex and demanding environments. This work is an introduction to some of the complex range of phenomena resulting from the combined effects of the Nuclear Magnetic Resonance (NMR) technique, relaxation, diffusion and porous media, with a particular focus on their applications in LWD conditions. Its aim is threefold. First, extracting information from porous media structure requires the development of theoretical models that connect its physical features to the NMR signal. In this regard, theoretical studies were conducted to describe the standard theory behind NMR relaxation and diffusion in porous media. Second, proper interpretation of experimental results remains challenging, in part due to the ill-posed inverse problem related to estimating some parameters from the NMR measurements. In this sense, we have applied the Tikhonov regularization method for parameter estimation. Third, singlesided magnets as a structure probe, in particular, allow one to simulate a petrophysics environment within the laboratory. In this respect, from an experimental perspective, preliminary measurements of a standard liquid were performed to determine the transverse relaxation time (T2) distributions probed by a benchtop single-sided NMR system, with well-logging tool characteristics: a cylindrical sweet spot with 4 cm of diameter and length; magnetic field of 47 mT centered at 11 cm from the magnets surface; and a constant gradient of 35.7 G/cm along z. To mimic the operation of an LWD tool, but under standard pressure and temperature conditions, we have established a controlled environment with a mechanical system capable of performing a sinusoidal motion between the sample and the external magnetic field. Our aim is to gain a deeper understanding of the complex patterns within the NMR signal in these scenarios by uncovering their underlying origins and drawing attention to potential caveats associated with the conventional interpretation of NMR relaxation data. Finally, in conclusion, ongoing research is under developing to address extreme conditions that push the frontiers of standard NMR theory, potentially aiding to industrial applications.